Online Brazilian Journal of Nursing - Cruz, Isabel Cristina Fonseca da (Online Brazilian Journal of Nursing, 2004)
This editorial is devoted to celebrate the anniversary of the Aurora de Afonso Costa School of Nursing (AACSN), at Fluminense Federal University (FFU). Rich in history, the AACSN celebrates its sixtieth year in 2004 meeting the health challenges of our developing country. An undergraduate program was first offered by the School of Nursing in 1944. The AACSN alumni impact the State of Rio de Janeiro, the nation and the world in health care delivery because they are prepared to be highly educated nurse leaders in research, teaching, training and care. So, practicing nurses play an essential role in linking the findings of research with the communities in which they work.The AACSN completed 60 years and will continue with the primary goals of excellence in nursing education, research and practice, as well as a commitment to service. In 1979, the AACSN initiated its first graduate experience: a nursing service administration certificate course, lato sensu graduate program, leading to a specialist degree. The School added programs in succeeding years that were created and coordinated by Dr. Isabel Cruz: Health Promotion (1994), Intensive Care, Renal Substitutive Therapies (2000), and Professional Master of Science (2003).We invite you to learn more about our School's three major departments, the Master Degree Program, and our Antonio Pedro University Hospital. Please, visit the Jane da Fonseca Proença Nursing Library.Read the NEPAE-NESEN the newsletter published by 2 School of Nursing´s research groups and check out the Online Brazilian Journal of Nursing, a scholarly peer-reviewed journal with free-access, for an inside look at the School of Nursing Professional Master´s Degree Program and our research production.The AACSN nursing faculty provide education and research training in the social, behavioral, and biological sciences focused on health, illness, and health care, and offer innovative teaching-learning strategies:a. on-city “labs” that prepare students from culturally diverse backgrounds for real life hospital or community clinical situations;b. evidenced-based practice integrated into campus classroom discussions;c. and student cultural emersion in Oriximiná - FFU campus, at Amazonian region.As you can see, the AACSN undergraduate (bachelor degree) and graduate (master´s degree) programs prepare students from the beginning generalist to the advanced practice nurse and the nurse scientist. The AACSN nursing research is recognized nationally for answering questions related to African-Brazilian health and institutional racism, women and children topics (Rosalda Paim, RN, PhD, Full Professor [former]), mental health, and other themes. The AACSN nursing faculty and students benefit the public, the profession, and the University through active individual and group involvement in service activities, promoting and demonstrating excellence in professional nursing practice. Taking advantage of its long history as a part of the Fluminense Federal University, the AACSN will continue to work cooperatively with other health professionals on campus, nationally, and internationally in its search for excellence in teaching, research, practice, and public service.Happy anniversary to the AACSN and a happy new year for all!